1996
DOI: 10.1007/bf00436568
|View full text |Cite
|
Sign up to set email alerts
|

Killer factor interference in mixed opportunistic yeast cultures

Abstract: The interaction of the killer yeast Pichia anomala UP 25F with the killer toxin-sensitive clinical isolate Candida albicans UCSC 10S and its natural toxin-resistant mutant derivative C. albicans UCSC 10R were studied under various conditions. A differential inhibition was shown to occur in vitro at pH and temperature values, which are not encountered in vivo, only by using preformed killer toxin, since antagonism due to yeast growth proved to be predominant on the killer effect. Under adverse growth conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Although a therapeutically attractive tool for its wide spectrum of microbicidal activity in vitro, inclusive of such diverse pathogens as Candida albicans, Pneumocystis carinii, and Mycobacterium tuberculosis, KT is by itself of no practical use because of its instability in the physiological milieu of mammals as well as its antigenicity and toxicity (2,8,22,25). We postulated the possibility of exploiting KT antimicrobial activity without KT's undesired effects by mimicry through the Id network (4,14).…”
mentioning
confidence: 99%
“…Although a therapeutically attractive tool for its wide spectrum of microbicidal activity in vitro, inclusive of such diverse pathogens as Candida albicans, Pneumocystis carinii, and Mycobacterium tuberculosis, KT is by itself of no practical use because of its instability in the physiological milieu of mammals as well as its antigenicity and toxicity (2,8,22,25). We postulated the possibility of exploiting KT antimicrobial activity without KT's undesired effects by mimicry through the Id network (4,14).…”
mentioning
confidence: 99%
“…The 50× concentrated KT, to be used as reference antigen in ELISA, was tested for killer activity by a conventional well assay against C. albicans UP10S, employed as reference KT-susceptible strain throughout the study [20].…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro candidacidal activity of the selected mAb and sera from immunized animals against C. albicans UP10S were carried out by conventional colony forming unit (CFU) assays [20]. Briefly, 10 µl of H 2 O containing ∼2–3×10 2 germinating yeast cells (expected number of CFU in the controls) were added to 90 µl of H 2 O in the presence or absence (control growth) of the purified mAb (final concentration 100 µg) or different dilutions of sera from immunized animals.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that killer yeasts are more abundant in natural habitats than in culture collections. It has been postulated that this may be due to the advantage that killer yeasts may have over sensitive strains in mixed cultures (Young, 1987; Conti et al , 1996; Marquina et al , 2002; Golubev, 2006). In addition, since some killer toxins are encoded by extra‐chromosomal DNA or RNA (plasmids), it is possible that these are lost during many cycles of cell proliferation in the laboratory environment (Fukuhara, 1995; Schmitt & Breinig, 2002; Golubev, 2006).…”
Section: The Use Of Ksps As a Yeast Biotyping Tool: Ecological Implicmentioning
confidence: 99%